2021
DOI: 10.1016/j.kint.2020.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Management of idiopathic childhood nephrotic syndrome in sub-Saharan Africa: Ibadan consensus statement

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…In the United Kingdom, a study had shown that NIS was 6 times more common in children of Asian origin than in European children [5]. In sub-Saharan Africa, nephrotic syndrome is the main cause of chronic renal failure and end-stage renal disease in children [6]. In multiracial countries, people of African descent have been shown to be at higher risk of developing steroid-resistant nephrotic syndrome [6] [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United Kingdom, a study had shown that NIS was 6 times more common in children of Asian origin than in European children [5]. In sub-Saharan Africa, nephrotic syndrome is the main cause of chronic renal failure and end-stage renal disease in children [6]. In multiracial countries, people of African descent have been shown to be at higher risk of developing steroid-resistant nephrotic syndrome [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotic syndromes can occur at any age, but begins most often (in 90% of cases) in children under 10 years of age, often after an infectious or allergic trigger [5]. Kidney biopsy is indicated in cases of atypia: child under 1 year or over 12 years old, macroscopic hematuria, severe arterial hypertension, extrarenal signs, hypocomplementemia, renal failure, positive hepatitis serology [6] [8] [9]. Pathologically, minimal glomerular lesions present the most common appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Both duration of the treatment and GS initial dose are matters of discussion. Two-, 3- and 6-month regimens have been used with conflicting data on the optimal treatment span [ 3 , 4 ], though recent studies [ 5 , 6 ] and guidelines [ 7 , 8 ]suggest short treatment duration in the majority of affected children.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently the Human Hereditary and Health in Africa-Kidney Disease Research Network (H3A-KDRN), generated a consensus statement on the management of childhood NS in sub-Saharan Africa using the modi ed Delphi approach to limit the observed variability in the management of childhood NS in Africa. [19] Among Caucasian children with NS, more than 85-90% of children are initially steroid sensitive and achieve remission within 4-6 weeks and 10-15% are initially steroid resistant (SR) [10,13,18]. The picture in Tropical Africa was characterized by paucity of MCD and steroid resistance in the 1960s to 1980s but recent reports are pointing to increasing steroid responsiveness in Sub-Saharan Africa as a whole [7,[20][21][22][23][24][25][26]).…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] In low-and middle-income countries in Africa where patients may not afford the expensive alternative immunosuppressive agents this drug may be a useful alternative. [19,31] It is known that there are disparities in the epidemiology and response to treatment in various clinical conditions [32], it is therefore necessary to evaluate the e cacy of the drug in Africa and if found e cacious, it will improve access to appropriate management and quality of life of these patients.…”
Section: Introductionmentioning
confidence: 99%